Circular RNA in liver cancer research: biogenesis, functions, and roles - Wang, Jiayi; Zhang, Congcong; Zhang, Yinghui; Guo, Jiaojiao; Xie, Chenyu; Liu, Yulu; Chen, Lidian; Ma, Liangliang (Frontiers in Oncology, 2025)
Liver cancer, characterized by its insidious nature, aggressive invasiveness, and propensity for metastasis, has witnessed a sustained increase in both incidence and mortality rates in recent years, underscoring the urgent need for innovative diagnostic and therapeutic approaches. Emerging research indicates that CircRNAs (circular RNAs) are abundantly and stably present within cells, with their expression levels closely associated with the progression of various malignancies, including hepatocellular carcinoma. In the context of liver cancer progression, circRNAs exhibit promising potential as highly sensitive diagnostic biomarkers, offering novel avenues for early detection, and also function as pivotal regulatory factors within the carcinogenic process. This study endeavors to elucidate the biogenesis, functional roles, and underlying mechanisms of circRNAs in hepatocellular carcinoma, thereby providing a fresh perspective on the pathogenesis of liver cancer and laying a robust foundation for the development of more precise and effective early diagnostic tools and therapeutic strategies.